2021
DOI: 10.1186/s12913-021-06302-w
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the differences in ICD and hospital morbidity data collection features across countries: an international survey

Abstract: Background The International Classification of Diseases (ICD) is the reference standard for reporting diseases and health conditions globally. Variations in ICD use and data collection across countries can hinder meaningful comparisons of morbidity data. Thus, we aimed to characterize ICD and hospital morbidity data collection features worldwide. Methods An online questionnaire was created to poll the World Health Organization (WHO) member countrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 19 publications
1
18
0
Order By: Relevance
“…The results of our study unveil that implementing appropriate coding policies enhances the satisfaction levels of coders and improves coding practice. This finding complies with the study of Otero Varela et al which revealed that lacking coding standards have negatively impacted the quality of clinical coding [23].…”
Section: Discussionsupporting
confidence: 92%
“…The results of our study unveil that implementing appropriate coding policies enhances the satisfaction levels of coders and improves coding practice. This finding complies with the study of Otero Varela et al which revealed that lacking coding standards have negatively impacted the quality of clinical coding [23].…”
Section: Discussionsupporting
confidence: 92%
“…EHRs' implementation strategies heavily rely on interoperable systems and platforms, which also account for IoT-related tools and services (I1 + , I2 + ) 22 38 47 48 49 50 51 52…”
Section: Resultsmentioning
confidence: 99%
“…There is also considerable worldwide variability in the use of the ICD versions, with some countries implementing “clinical modifications” that modify ICD codes according to country-specific needs, e.g., ICD-9-CM and ICD-10-CM in the US, or ICD-10-CA in Canada (Otero Varela et al, 2021 ). These modifications can either include more detailed coding to characterize a patient’s state (generating more individual codes than the original version) or be used to simplify the index terms of the ICD.…”
Section: Critical Appraisal Of Methodological Approachesmentioning
confidence: 99%